The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/boneres.2015.5
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β/BMP signaling and other molecular events: regulation of osteoblastogenesis and bone formation

Abstract: Transforming growth factor-beta (TGF-β)/bone morphogenetic protein (BMP) plays a fundamental role in the regulation of bone organogenesis through the activation of receptor serine/threonine kinases. Perturbations of TGF-β/BMP activity are almost invariably linked to a wide variety of clinical outcomes, i.e., skeletal, extra skeletal anomalies, autoimmune, cancer, and cardiovascular diseases. Phosphorylation of TGF-β (I/II) or BMP receptors activates intracellular downstream Smads, the transducer of TGF-β/BMP s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
390
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 484 publications
(421 citation statements)
references
References 179 publications
8
390
1
8
Order By: Relevance
“…Runx2 and Osx are important transcription factors for osteoblast differentiation and bone formation [16][17][18]. BMP-2 signal is known to increase expressions of Runx2 and Osx in osteoblasts [1,2], and in our study, we also confirmed that BMP-2 significantly increased both Runx2 and Osx in MC3T3-E1 cells. Interestingly, AMPK inhibition significantly reversed the expression of Runx2, whereas it did not affect the expression of Osx.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Runx2 and Osx are important transcription factors for osteoblast differentiation and bone formation [16][17][18]. BMP-2 signal is known to increase expressions of Runx2 and Osx in osteoblasts [1,2], and in our study, we also confirmed that BMP-2 significantly increased both Runx2 and Osx in MC3T3-E1 cells. Interestingly, AMPK inhibition significantly reversed the expression of Runx2, whereas it did not affect the expression of Osx.…”
Section: Discussionsupporting
confidence: 78%
“…belong to transforming growth factor-β superfamily, bind to BMP receptors and transduce signals [1,2]. BMPs are known to be powerful osteo-inductive cytokines, and numerous studies have shown that BMP-2, one of BMP family members, enhances osteoblastic differentiation and mineralization through Smad signals and non-Smad pathways such as mitogen-activated protein kinase (MAPK) [1,2].…”
Section: Bone Morphogenetic Proteins (Bmps)mentioning
confidence: 99%
See 1 more Smart Citation
“…receptor activator of NFκB ligand (RANKL)], and related pathways [e.g. mitogen-activated protein kinase (MAPK)] (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β acts through the heteromeric receptor complex, comprised of type I and type II receptors at the cell surface that transduces intracellular signals by Smad complex or MAPK cascade (12)(13)(14)(15)(16)(17). At least 29 and probably up to 42 TGF-β, five type II receptors and seven type I receptors are encoded by the human genome (18,19).…”
Section: Effect Of Bmp/ Tgf-βs Pathway On Osteogenitor Cellsmentioning
confidence: 99%